Membranous nephropathy and thymoma in a patient with ankylosing spondylitis: A case report. Issue 18 (May 2020) - Lin, Lirong; Zhao, Lei; Huo, Bengang; Zheng, Luquan; Yu, Rongjie; Li, Weibing; Yang, Jurong
Abstract: Rationale: We report a rare case with ankylosing spondylitis (AS), thymoma, and membranous glomerulonephritis. The pathogenic mechanisms of these 3 diseases may be associated with each other. Here, we discuss the course of diagnosis and treatment. Patient concerns: A 64-year-old woman with bilateral pain of the sacroiliac joints for 10 years and anasarca for 10 days. Diagnoses: A diagnosis of AS by HLA-B27 and pelvic X-ray tests, thymoma based on computed tomography and pathological diagnosis, and membranous glomerulonephritis based on renal biopsy. Interventions: We administered methylprednisolone 500 mg/d for 3 consecutive days, followed by methylprednisolone 40 mg oral QD, for a month. Outcomes: The patient was followed up once a month. In the sixth month, the patient's serum creatinine had decreased to 0.96 mg/dL, urine microalbumin/creatinine decreased to 173.3 mg/g, and albumin had risen to 33.1 g/L. Pain and morning stiffness were relieved, and the Bath Ankylosing Spondylitis Disease Activity Index score dropped to 4.0. Lessons: Although the causal relationship between AS, thymoma, and membranous nephropathy in this patient still needs to be established, the pathogenesis between the 3 diseases may have some association. In clinical practice, patients with AS need to be screened for tumors and renal complications.